THE HISTORY LINGUISTICS.DEVELOPMENT OF ANCIENT LINGUISTICS - Mamarasulova Iroda; Asadullayeva Nargiza; Qushboqova Sevinch (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article provides information about the emergence of linguistic teaching and its development in different countries.